Aqueous synthesis of polyhedral "brick-like" iron oxide nanoparticles for hyperthermia and T2 MRI contrast enhancement1. Issue 34 (14th September 2015) - Worden, Matthew; Bruckman, Michael A.; Kim, Min-Ho; Steinmetz, Nicole F.; Kikkawa, James M.; LaSpina, Catherine; Hegmann, Torsten
<x xml:space="preserve">Abstract</x> Iron oxide nanobricks prepared by co-precipitation in lyotropic liquid crystal phases are versatile and effective theranostic materials for magnetic hyperthermia, T2 MRI contrast enhancement and differential cell internalization.